2022
DOI: 10.1177/20503121221105579
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of catatonia: A prospective study in urban South Africa

Abstract: Objectives: Rapid intervention for catatonia with benzodiazepines and electroconvulsive therapy can prevent fatal complications. We describe the management and treatment response of 44 patients with catatonia in a psychiatric unit in urban South Africa. The objective was to screen admissions for catatonia and investigate management, treatment response, and treatment outcomes. Method: We used a prospective, descriptive, observational study design and collected data using a data collection sheet, the Bush Franci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…There are only a few data with regard to the recurrence of catatonia, but it has been suggested that the rate of relapses and recurrences are likely underestimated [56]. In a very recent prospective, observational study in an acute mental health unit in South Africa, the recurrence rate of catatonia over an 8-week follow-up was 2.3%, but involved just one patient [57]. Other research suggests that recurrence mostly involves the retarded catatonia subtype which responds well to benzodiazepines [56], and shows consistency of the catatonic signs and symptoms across different episodes [58].…”
Section: Relapse and Recurrencementioning
confidence: 99%
“…There are only a few data with regard to the recurrence of catatonia, but it has been suggested that the rate of relapses and recurrences are likely underestimated [56]. In a very recent prospective, observational study in an acute mental health unit in South Africa, the recurrence rate of catatonia over an 8-week follow-up was 2.3%, but involved just one patient [57]. Other research suggests that recurrence mostly involves the retarded catatonia subtype which responds well to benzodiazepines [56], and shows consistency of the catatonic signs and symptoms across different episodes [58].…”
Section: Relapse and Recurrencementioning
confidence: 99%